A new speleothem record of the penultimate deglacial: Insights into spatial variability and centennial-scale instabilities of East Asian monsoon. (15th April 2019) - Xue, Gang; Cai, Yanjun; Ma, Le; Cheng, Xing; Cheng, Hai; Edwards, R. Lawrence; Li, Dong; Tan, Liangcheng
Abstract: We present a highly resolved oxygen isotope (δ 18 O) record of the penultimate glacial-interglacial transition from a 230 Th-dated stalagmite (SD1) from the Shangxiaofeng Cave in north-eastern China. Our δ 18 O record reveals two prominent features. First, the SD1 δ 18 O record documents a brief increase of δ 18 O between 128.5 and 128.1 ka BP. Though this event has been identified in several marine records, our radiogenic dated record precisely constraints the timing and duration of the climate deterioration suggesting that this YD-like event is likely an intrinsic feature of climate change during the ice age terminations. Additionally, the δ 18 O magnitude of the glacial-interglacial change (∼0.7‰) is significantly smaller compared to the δ 18 O records from inland and relatively high elevation caves (Dongge, Sanbao and Yangkou caves) (1.4–2.4‰) but comparable to the Hulu Cave at low elevation and proximal to the shallow Bohai and Yellow seas (Kelly et al., 2006; Cheng et al., 2006; Wang et al., 2008; Cheng et al., 2009; Li et al., 2014). Assuming that the cave δ 18 O records mainly reflect precipitation isotope composition changes, the glacial-interglacial speleothem δ 18 O difference between the various Chinese caves could be related to changes in atmospheric circulations, changing effect of altitude between the various caves and climate mean states, and large-scale changes in regional land-sea coverage due to sea level changes. The latter leads to disappearance and expansion of Bohai and Yellow seas during glacial and interglacial episodes, respectively, and likely affect the amount and isotope composition of precipitation. Taken together, our study highlights that hydroclimate imprints of the East Asian Monsoon changes during the penultimate glacial-interglacial cycle were spatially heterogeneous and centennial-scale monsoonal hydroclimate instabilities are likely inherent features of deglacial climate transition. Highlights: A new and highly resolved δ 18 O record was investigated from northern China during penultimate deglaciation. A transient YD-like event is identified during the penultimate deglaciation. Coastline shift has substantial influences on the isotope composition of precipitation in Eastern China. Centennial-scale monsoonal hydroclimate instabilities are inherent features of deglacial climate transition.